Habitat Preferences of Lamp Shell (Lingula unguis) in Nambo Waters, Kendari City, Southeast Sulawesi: Preferensi Habitat Kerang Lentera (Lingula unguis) di Perairan Nambo, Kota Kendari, Sulawesi Tenggara - Taula, Taula; Findra, Muhammad Nur; Bahtiar, Bahtiar; Purnama, Muhammad Fajar (Habitus Aquatica, 2023)
Coastal resources of Nambo Waters in Kendari City include mangrove and seagrass ecosystems which provide ecological benefits for the life of benthic and other organisms. One of the benthic organisms utilized by local communities in Nambo is the lamp shells. This study aimed at determining the habitat preferences of lamp shells in Nambo Waters. The sampling was conducted twice a month, applying the systematic random sampling method. Density, distribution patterns and size distributions were analyzed. Habitat preferences of lamp shells was analyzed using the Coresponden Analysis (CA) and Principle Component Analysis (PCA) to determined the water parameter characteristics were done by apllying the XLSTAT 2014 program. The result of analysis showed the number of density ranged from 1,06-10,44 ind/m2. The distribution pattern index suggested that lamp shells have random and uniformed distribution patterns. The distribution of total length sizes (shell length and pedicle) of the lamp shells was divided into 10 size classes, dominated by shells with 77–102 mm in sizes. The habitat preferences of lamp shells was characterized by the texture of medium and muddy sand substrates in mangrove ecosystem.